1985
DOI: 10.1115/1.3239695
|View full text |Cite
|
Sign up to set email alerts
|

Optical Measurements of Soot Size and Number Density in a Spray-Atomized, Swirl-Stabilized Combustor

Abstract: In-flame optical measurements of soot particulates in a turbulent, recirculating (i.e., complex flow) model laboratory combustor are described. A nonintrusive optical probe based on large-angle (60 and 20 deg) intensity ratio scattering was used to yield a point measurement of soot particulate in the size range of 0.08 to 0.38 μm. A shale-derived JP-8 stock, isooctane, and mixtures of isooctane with various ring and aromatic compounds blended to yield the smoke point of the JP-8 stock were separately injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Turbo (High Temperature Gas Turbine) programme funded by the Bundesministerium fur Forschung und Technologie (BMFT). Electron microscope picture of a soot sample extracted from with those obtained by Wood and Samuelson [24], who, moreover, found corresponding particle sizes. Additionally, electron microscopy was applied to soot particles which were sampled by means of Nuclepore filters.…”
Section: In Situ Measurements In a Liquid Fuel-fired Atmospheric Combmentioning
confidence: 52%
“…Turbo (High Temperature Gas Turbine) programme funded by the Bundesministerium fur Forschung und Technologie (BMFT). Electron microscope picture of a soot sample extracted from with those obtained by Wood and Samuelson [24], who, moreover, found corresponding particle sizes. Additionally, electron microscopy was applied to soot particles which were sampled by means of Nuclepore filters.…”
Section: In Situ Measurements In a Liquid Fuel-fired Atmospheric Combmentioning
confidence: 52%
“…Previous studies, for example, demonstrated that dome region mixing is sensitive to the manner by which the fuel is introduced (Charles et al, 1986). As additional evidence of this, the formation and emission of soot particulate has been shown to be strongly influenced by NAF ratio in liquid-fueled model combustors (Wood and Samuelsen, 1985). The geometry of the dome has also been shown to affect mixing (Charles et al, 1986).…”
Section: Parametric Variationmentioning
confidence: 93%